Hard and Soft Infrastructure as Determinants of Destinations’ Competition: The Moderating Effect of Mobile Technology - Wei Chiang, Chan (Universiti Malaysia Sarawak, 2022)
The tourism industry involves a wide range of industry and has undergone extraordinary growth for the past 50 years. To this, measuring destination competitiveness has become a substantial interest for the tourism stakeholders. Hard and soft infrastructure as critical determinants of destination competitiveness is an important topic to study and improve. Besides, adopting new technology like mobile technology by the tourism service provider can enhance the travel experience of tourists. However, Malaysia currently faces several problems regarding destination competitiveness and infrastructure development, such as diminishing destination competitiveness ranking, poor hard infrastructure development in Sarawak, and limited study on soft infrastructure toward destination competitiveness. Hence, the main objective of this study is to investigate the importance of hard and soft infrastructures as determinants to destination competitiveness with the moderating effect of ICT tool (mobile technology) from the perspective of visitors. The research was conducted at ecotourism sites: Bako National Park, Semenggoh Nature reserve, Matang Wildlife Centre, Gunung Mulu National Park, and Niah National Park. A total of 194 sets of data were collected from these selected ecotourism sites. After preliminary data analysis, only 190 sets of data are valid for further analysis. For the statistical analysis of this study, software such as SPSS 26.0 and WarpPLS 7.0 were utilized. SPSS 26.0 was used to perform preliminary analysis, and WarpPLS 7.0 to perform partial least square structural equation modelling (PLS-SEM) and estimate the relationships between the constructs. The findings revealed that five out of twelve of the proposed hypotheses were found to be supported. Three of the hard and soft infrastructure, transportation, accommodation, and health services, were found to have a significant and positive relationship toward destination competitiveness. Besides, mobile technology moderates the relationship between telecommunication infrastructure and government tourism policy toward destination competitiveness. The discoveries of the current study contributed to the scholars and practitioners by equipping valuable information supported by empirical evidence on the moderating effect of mobile technology and the direct relationship between infrastructures and destination competitiveness.